FAKTOR - FAKTOR YANG MEMPENGARUHI ANGKA KEJADIAN TINEA PEDIS PERKEBUNAN KELAPA SAWIT DI DESA SONOMARTANI KECAMATAN KUALUH HULU KABUPATEN LABUHAN BATU UTARA SUMATERA UTARA - SELA HARYANI; DIAN ERISYAWANTI BATUBARA (LP2MTBM MAKARIOZ, 2021)
This type of research is descriptive with a cross-sectional design, where the dependent variable and independent variabledata are taken at the same time. This study uses primary data obtained from the results of structured interviews and guidedby questionnaires, on farm laborers of oil palm plantations in Sonomartani Village, Labuhan Batu Utara Regency. The studydesign was carried out by measuring simultaneously (once upon a time). The research results were obtained after takingdata from farmers in oil palm plantations in Sonomartani Village, Kualuh Hulu District, Labuhan Batu Regency, NorthSumatra, North Sumatra. This research has obtained a health research ethics committee, the Faculty of Medicine,Muhammadiyah University of North Sumatra, with number 363 / KEPK / FKUMSU / 2019. There is a relationship betweenthere is a relationship between the level of education, length of use of shoes, frequency of bathing twice a day, cleaning andrubbing feet, and bathing using soap with the factors of tinea pedis in Sonomartani Village Kualuh Hulu District Labuhan BatuUtara Regency.